PATHWAYS FROM DIGITAL USE AND FAMILY SUPPORT TO SCIENCE ACHIEVEMENT AND SCIENCE ATTITUDES: THE ROLE OF CURIOSITY IN PISA 2022 - trisna, silvi; husna, husna; Rahmi, Aidhia (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2026)
Digital learning environments and family support are an important part of student learning success. However, the relationship between technology use, family roles, and student achievement is not always directly related. There are other factors that influence such as students' curiosity and attitude towards science. Purpose of this study is to analyze the relationship between digital use, family support, curiosity, science attitudes, and student achievement using PISA 2022 data. The research uses a quantitative approach based on secondary data, analyzed through path analysis with maximum likelihood estimation. The results of the study found a positive relationship between family support and curiosity, attitudes towards science, and student achievement. Digital use has relatively little relationship with curiosity and attitudes towards science. Curiosity plays a role as a psychological factor that has a positive relationship with students' scientific attitudes and achievement. Therefore, digital technology should not only be understood as a learning tool, but also as a means to encourage exploration, build curiosity, and create more meaningful learning engagement. This study enriches PISA-based studies by showing that curiosity can be an important link between the digital environment, family support, and student learning outcomes.